2019
DOI: 10.4103/ijpvm.ijpvm_166_18
|View full text |Cite
|
Sign up to set email alerts
|

Depression literacy in urban and suburban residents of Tehran, the Capital of Iran; Recognition, help seeking and stigmatizing attitude and the predicting factors

Abstract: Background: Recognizing the mental health literacy condition among the people is an important step towards promotion of mental health of a society. This study has been conducted to evaluate the depression literacy among Tehran city and its suburban residents. Methods: This is a cross-sectional study of 18- to 68-year-old residents in Tehran city and suburb in 2017. Sampling in Tehran city was conducted using Random Digit Dialing (RDD) and 1340 people were recruited. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
4
5
1
2
Order By: Relevance
“…The results of this study showed that there was a significant relationship between sex and MHL, and MHL was higher in women than men. The results of this study were consistent with the results of other The results of various studies showed that women had a higher level of MHL than men [42,43], had a greater ability to recognize mental disorders [40,44], and were more likely to seek professional mental health services than men [45]. Also, women tend to know more about mental health and are more inclined to interact with people with mental disorders [46,47].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of this study showed that there was a significant relationship between sex and MHL, and MHL was higher in women than men. The results of this study were consistent with the results of other The results of various studies showed that women had a higher level of MHL than men [42,43], had a greater ability to recognize mental disorders [40,44], and were more likely to seek professional mental health services than men [45]. Also, women tend to know more about mental health and are more inclined to interact with people with mental disorders [46,47].…”
Section: Discussionsupporting
confidence: 90%
“…The results of another study showed that people who helped search for mental health received their required information from family and friends rather than mental health professionals [39]. The results of Ghadirian's study also showed that most people had asked friends and family for help when using mental health services, respectively [40]. People achieve mental health information from various sources that may not be reliable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gender difference was observed for all three illnesses, not only for schizophrenia. This may be in line with previous studies which observed the same trend in the general population [47][48][49][50][51][52][53]. In contrast to the gender difference, the level of education in teachers did not have a significant effect on knowledge score and recognition of specific mental illnesses.…”
Section: Discussionsupporting
confidence: 91%